Co-management of domestic wastewater and food waste: A life cycle comparison of alternative food waste diversion strategies. (January 2017) - Becker, Adilson M.; Yu, Kevin; Stadler, Lauren B.; Smith, Adam L.
Graphical abstract: Highlights: Co-digestion and AnMBR treatment of food waste maximizes energy recovery. Co-digestion minimizes global warming impacts by preventing fugitive gas emissions. Composting food waste negatively impacts respiratory effects and eutrophication. Energy recovery for AnMBR is sensitive to food waste diversion participation. Abstract: Food waste is increasingly viewed as a resource that should be diverted from landfills. This study used life cycle assessment to compare co-management of food waste and domestic wastewater using anaerobic membrane bioreactor (AnMBR) against conventional activated sludge (CAS) and high rate activated sludge (HRAS) with three disposal options for food waste: landfilling (LF), anaerobic digestion (AD), and composting (CP). Based on the net energy balance (NEB), AnMBR and HRAS/AD were the most attractive scenarios due to cogeneration of produced biogas. However, cogeneration negatively impacted carcinogenics, non-carcinogenics, and ozone depletion, illustrating unavoidable tradeoffs between energy recovery from biogas and environmental impacts. Fugitive emissions of methane severely increased global warming impacts of all scenarios except HRAS/AD with AnMBR particularly affected by effluent dissolved methane emissions. AnMBR was also most sensitive to food waste diversion participation, with 40% diversion necessary to achieve a positive NEB at the current state of development.